2014
DOI: 10.1097/brs.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Stability of Lateral Interbody Implants and Supplemental Fixation in a Cadaveric Degenerative Spondylolisthesis Model

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…On the other hand, there are several biomechanical studies using cadaveric spine models which compared the stability of the LLIF with or without posterior instrumentation. These studies showed that both the addition of unilateral and bilateral PPS produced a significant decrease in range of motion, compared www.nature.com/scientificreports www.nature.com/scientificreports/ with the standalone cages, in all axes of motion [27][28][29][30] . Finally, they concluded that surgeons should choose fixation options commensurate with the stability requirements of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are several biomechanical studies using cadaveric spine models which compared the stability of the LLIF with or without posterior instrumentation. These studies showed that both the addition of unilateral and bilateral PPS produced a significant decrease in range of motion, compared www.nature.com/scientificreports www.nature.com/scientificreports/ with the standalone cages, in all axes of motion [27][28][29][30] . Finally, they concluded that surgeons should choose fixation options commensurate with the stability requirements of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive unilateral PSF (UPSF), facet screw fixation (FSF), facet wedging, integrated lateral screws, lateral plating, and ISPF have all been studied. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The latter 2 fixation modalities, lateral plating and ISPF, were of particular interest in this study given their synergistic capabilities. While Fogel et al 8,9 and Reis et al 18 have previously assessed LLIF þ ISPF in vitro; plating was traditional independent fixation only.…”
Section: Discussionmentioning
confidence: 99%
“…Given such inherent structural benefits, it has been proposed that extensive and/or invasive posterior fixation could be unnecessary with LLIF. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Accordingly, increased consideration has been given to alternative, less invasive means to achieving stability with the lateral access technique. Two techniques of particular interest have been lateral plating and interspinous process fixation (ISPF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,23 Another pathology-related criterion has been studied in LLIF subsidence: poor bone quality. Similarly to the present study, Tempel et al 18 conducted a case-control study to analyze bone mineral density (BMD) in cases that evolved with subsidence following LLIF.…”
Section: Discussionmentioning
confidence: 99%